Editorial - Van Patten, Elia María (1982)
When editing the last newsletter of 1982 the Library Unit of the Faculty of Arts, is pleased to pay a farewell tribute to our coordinator Mr., Deyanira Sequeira, who is the founder of the School of Library Science at the University.She has been a tireless fighter for the professional advancement of members of the unit and the improvement of academic quality that exists in each and every one of the courses and teaching programs.We express our sincere appreciation for the work he did in the Unit Library for the benefit of the career of students, those who work with her, at the National University and the country in general.